Comparative Study of Oral Clonidine Versus Gabapentin as Premedication for Anxiolysis, Sedation and Attenuation of Pressor Response to Laryngoscopy and Tracheal Intubation - Hossain, Muhammad Sazzad; Rashid, Mohammad Mamunur; Islam, Syed Ariful; Babu, Md Anisur Rahman; Saha, Devashis; Islam, Nadia; Islam, Md Sirajul; Chowdhury, M Alamgir (Anwer Khan Modern Medical College Journal, 2018)
Background and Aims: We conducted a prospective, randomized, double-blind and controlled trial to compare the effects of oral clonidine and gabapentin as premedication in obtunding hemodynamic response to laryngoscopy and intubation in normotensive patients undergoing elective surgery. We also compared the preoperative anxiety and sedation status between these two drugs. Materials and Methods: A total of 60 patients of American Society of Anesthesiologists (ASA) physical status I, aged 20 -50 years of either sex enrolled in the study were randomly divided into two groups of 30 each. Group A patients received oral clonidine 200 mcg and Group B patients received oral gabapentin 900 mg, 90 minutes prior to induction of anesthesia. The heart rate, systolic blood pressure, diastolic blood pressure and mean arterial pressure were observed and recorded pre and post endotracheal intubation. Anxiety and sedation score were noted after 60 minutes of oral administration of drug as well as before induction of anesthesia. Results: Both groups were matched for age, sex, weight and intubation time. Anxiety score and sedation score before induction were significantly better in clonidine group as compared with gabapentin group. Also oral clonidine attenuated the increase in heart rate, systolic blood pressure, diastolic blood pressure and mean arterial pressure better than oral gabapentin (p<0.05). Conclusion: Oral clonidine provided good attenuation of hemodynamic response to laryngoscopy and intubation as compared with oral gabapentin. Also clonidine is better agent as anxiolytic and sedative than gabapentin. Anwer Khan Modern Medical College Journal Vol. 9, No. 2: Jul 2018, P 131-136